Pengaruh Kualitas Kehidupan Kerja, Komunikasi Organisasi, Dan Kepuasan Kerja Terhadap Kinerja Karyawan - Nasrul Nur Hidayat (PT Ilmu Data Indonesia, 2025)
This study aims to investigate the impact of quality of work life, organizational communication, and job satisfaction on employee performance at Preksu Ayam Geprek Susu. With a population of 40 employees, the study used a nonprobability sampling method with a purpose sampling technique (saturated sampling), which selects the entire population as a sample. The data obtained was analyzed using multiple linear regression tests. The results showed that the quality of work life, organizational communication, and job satisfaction together have a significant influence on employee performance. This shows that these elements influence each other in creating optimal performance in the workplace. This study makes an important contribution to the understanding of the factors that affect employee performance, especially in business environments such as Preksu Ayam Geprek Susu. Thus, management can pay attention and improve these aspects to improve overall organizational performance. The result of this reseach highlights the importance of paying attention to nonfinancial factors such as job satisfaction and organizational communication in improving employee productivity and wellbeing.